Airflow mixing augmentation device for hot-air heating systems in modular boilers; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Kurilenko N. I. Nikolay; Artamonov P. A. Pavel; Kurilenko E. Yu. Elena; Mamontov G. Ya. Gennady Yakovlevich (2017, 2017)
Title screen